EDUKASI PENGGUNAAN GAWAI YANG SEHAT DALAM UPAYA PENCEGAHAN GANGGUAN KESEHATAN MATA PADA SISWA SMA X MELAYA BALI - Niluh Nyoman Tantri Swastikaningtyas; Putu Adi Cahya Dewi; Pande Putu Indah Purnamayanthi (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2026)
Gadget use among teenagers is currently increasingly intensive, especially when it is often used in the learning process. However, excessive gadget use poses a risk to eye health. Prolonged screen exposure can cause complaints such as tired eyes, dry eyes, blurred vision, headaches, and a decrease in the quality of life of teenagers. The purpose of this community service is to increase knowledge and awareness of high school/vocational school teenagers regarding the dangers of gadget addiction and the importance of maintaining eye health. The methods used include health counseling, interactive education, discussions, and providing materials on the impact of excessive gadget use, the application of the 20-20-20 rule to reduce eye fatigue, managing gadget use time, and the importance of physical activity and adequate rest. The activity was carried out on high school/vocational school students with a participatory approach. The results of the activity showed an increase in participants' understanding of the risks of gadget addiction and its impact on eye health. Participants also understood the steps to prevent vision problems due to uncontrolled gadget use. This health education is expected to shape healthier gadget use behaviors that can maintain eye health and support optimal adolescent growth and development.